Time to Completion of Pediatric PROMIS Computerized Adaptive Testing Measures and the SRS-22r in an Adolescent Idiopathic Scoliosis Population. Issue 9 (16th October 2022) - Paranjape, Chinmay S.; de Araujo, Olivia B.; Reider, Lisa M.; Sponseller, Paul D.; Carlini, Anthony R.; McLaughlin, Kevin; Bachmann, Keith R.; Mitchell, Stuart L.
Abstract : Background: Patient-reported outcome measures are useful tools to quantify patients' pre-treatment and post-treatment symptoms. Historically used "legacy measures", such as the Scoliosis Research Society-22 revised questionnaire (SRS-22r), are often disease-specific and can be time-intensive. Recently developed Patient-Reported Outcomes Measurement Information System (PROMIS) computerized adaptive testing (CAT) measures may reduce administrative burdens and permit more efficient outcome collection within clinic workflows. In an era of medicine where payments are becoming tied to outcomes, we sought to assess the time to completion (TTC) of 8 pediatric PROMIS CAT measures and the SRS-22r in adolescents with idiopathic scoliosis. Materials and Methods: Patients presenting to a large, urban tertiary referral hospital were prospectively enrolled into the study. Subjects were first-time survey respondents in various phases and types of treatment for adolescent idiopathic scoliosis. In total, 200 patients ranging from 10 to 17 years old completed 8 Pediatric PROMIS CATs and the SRS-22r. PROMIS CATs administered include Physical Activity, Mobility, Anxiety, Depressive symptoms, Peer Relationships, Physical Stress Experiences, Pain Behavior and Pain Interference. TTC was calculated using start and stop timestamps in the REDCap software. Results: The mean (±SD) TTC for each PROMIS CAT was 1.1 (±0.9) minutes with physical activity, mobility, anxiety, depressive symptoms, peer relationships, physical stress experiences, pain behavior, and pain interference taking 1.2, 1.4, 1.0, 0.9, 1.2, 1.0, 1.0, and 1.2 minutes on average to complete, respectively. Mean TTC for the SRS-22r was 5.2 (±3.0) minutes. Conclusions: In this pediatric orthopaedic cohort, completion of 8 PROMIS CATs demonstrated minimal test-taker burden and time required for completion. These findings support rapid and easily integrable PROMIS CATs in clinical practice to aid in increased delivery of efficient, patient-centered care. Level of Evidence: III, cross-sectional study.